Benefícios de uma aula sobre prismas com a utilização de palitos e jujubas - FERNANDES, David Lucas Gomes Leão (2024)
This study aimed to verify the effectiveness of a class applied to 1st B high school students at E.E.E.F.M Professor Leonardo Negrão on triangular and quadrangular prisms based on their constructions using jelly beans to represent the vertices and toothpicks (tooth and barbecue) to represent the edges. For the theoretical framework, the ideas of Torrione (2004), Lorenzato (2003) and (2006) were brought, among others who defend the use of Manipulable Didactic Materials (MDMs) in the classroom. The data were collected using the participant observation method and the cell phone camera to respond to two indicators that guided the research, the first being called 'Class efficiency from the authors' point of view' and the second called 'Class efficiency from the authors' point of view'. of students', where the latter was asked for students to write their opinions on this pedagogical approach used in their notebook. As a result of these indicators, it was possible to observe that the students were interested in learning about triangular and quadrangular prisms such as the use of jelly beans and toothpicks, they remained concentrated during the explanation and built their prisms quickly. Therefore, with the application of this experiment, the present authors infer that using MDMs in teaching mathematics is a valid and efficient pedagogical approach, which should be implemented in teaching.